Proteomic profiling of lymphedema development in mouse model. (5th May 2016) - Lee, Joomin; Song, Haeun; Roh, Kangsan; Cho, Sungrae; Lee, Sukchan; Yeom, Chang‐Hwan; Park, Seyeon
Abstract : The lymphatic vascular system plays an important role in tissue fluid homeostasis. Lymphedema is a chronic, progressive, and incurable condition that leads to lymphatic fluid retention; it may be primary (heritable) or secondary (acquired) in nature. Although there is a growing understanding of lymphedema, methods for the prevention and treatment of lymphedema are still limited. In this study, we investigated differential protein expressions in sham‐operated and lymphedema‐operated mice for 3 days, using two‐dimensional gel electrophoresis (2‐DE) and mass spectrometry analysis. Male improved methodology for culturing noninbred (ICR) mice developed lymphedema in the right hindlimb. Twenty functional proteins were found to be differentially expressed between lymphedema induced‐right leg tissue and normal left leg tissue. Out of these proteins, the protein levels of apolipoprotein A‐1 preprotein, alpha‐actinin‐3, mCG21744, parkinson disease, serum amyloid P‐component precursor, annexin A8, mKIAA0098 protein, and fibrinogen beta chain precursor were differentially upregulated in the lymphedema mice compared with the sham‐operated group. Western blotting analysis was used to validate the proteomics results. Our results showing differential up‐regulation of serum amyloid P‐component precursor, parkinson disease, and apolipoprotein A‐1 preprotein in lymphedema model over sham‐operated model suggest important insights into pathophysiological target for lymphedema. Copyright © 2016 John Wiley & Sons, Ltd.